ORNAMENTAL VARIETIES OF GEDONG SONGO SEMARANG TEMPLE AS A TYPEFACE DESIGN INSPIRATION - Nugroho, Dany Prasetyo (Arty: Jurnal Seni Rupa, 2019)
In the era of modernization, the language of visual communication has a significant development. Visual communication devices have changed and moved with process capabilities and speeds are constantly updated, thus providing the convenience as well as challenges for the user by using these facilities in a timely manner. The discipline of Typography has an important role in determining a success of the art form of communication. Unfortunately, this discipline received less attention in the world of graphic design in Indonesia. As the response, the writer in the study project entitled "Decorative Variety at Gedong Songo Temple Semarang as Inspiration of Typeface Design" tries to contribute through typography work in the form of letters with decorative vines in Gedong Songo Temple Semarang as inspiration. The work is produced in the form of text letters and display letters and the application of it to various media and merchandise. From the whole process of design to the distribution of the work could be concluded that the authors are able to contribute through the design of typeface Gedong Songo to advance the world of typography of Indonesia and in the preservation of Indonesia's cultural heritage. expected through this project would inspire other designers to work as well as preserve the Indonesian cultural heritage, and can increase public awareness to participate in the preservation of Indonesian culture through their own way.